Dapatkah Harga dan Kualitas Pelayanan Berdampak Terhadap Minat Konsumen Pada Biro Perjalanan Haji dan Umroh? - Rizky Winanda; Nuri Herachwati; Ridan Muhtadi (LP2M IAI Miftahul Ulum Pamekasan, 2023)
This scientific article investigates the impact of price and quality of service on consumer interest in Hajj and Umrah travel agencies. The study aims to understand the factors that influence consumers' decision-making process when selecting travel agencies for their religious pilgrimages hajj and umrah. The research employs a quantitative approach, utilizing a structured questionnaire to collect data from a sample of potential pilgrims a hajj and umrah in PT. X. Statistical analysis techniques, including regression analysis, are employed to examine the relationships between price, quality of service, and consumer interest. The findings reveal that both price and quality of service significantly influence consumer interest in Hajj and Umrah travel agencies. Specifically, affordable pricing and superior service quality emerge as key drivers for consumers' selection of travel agencies. The study provides valuable insights for travel agencies to enhance their competitive advantage and attract more customers by strategically managing pricing strategies and improving service quality. Moreover, it contributes to the existing body of knowledge on consumer behavior within the context of religious tourism, particularly for the Hajj and Umrah market segment. Further research avenues are proposed to deepen the understanding of consumer preferences and behavior in this domain